Pituitary tumours in the elderly. - Turner, H; Wass, J (1997)
Pituitary tumours in the elderly are a neglected topic in the literature of endocrinology and gerontology. Data from autopsy studies in the elderly show that the commonest tumours are microadenomas, which are either immunocytochemically negative or stain for prolactin. Prolactin-secreting pituitary tumours, however, appear rarely in clinical series of patients in this age group and non-functioning adenomas are the commonest tumour seen, although pituitary metastasis and craniopharyngiomas also occur. Diagnosis can be difficult, but the commonest presentation is visual field loss. Hypopituitarism may be diagnosed late and incidental radiological diagnosis is not uncommon. There are few data which specifically answer the question, but there is a suggestion that the syndromes associated with hormonal hypersecretion may be milder in this age group. Conventional treatment with drugs, surgery and radiotherapy should be decided on an individual basis as these therapies appear to be well tolerated and beneficial in selected patients.